Statistics of the tripolar electrostatic solitary waves within magnetic reconnection diffusion region in the near‐Earth magnetotail. Issue 6 (3rd June 2013) - Li, S. Y.; Zhang, S. F.; Cai, H.; Chen, X. Q.; Deng, X. H.
Abstract : [1] In this paper, we report the observations and statistical characteristics of tripolar electrostatic solitary waves (ESWs) along the plasma sheet boundary layer near the magnetic reconnection X line in the near‐Earth magnetotail. Within reconnection diffusion region, the tripolar ESWs are ample and are continuously observed during one burst interval (8.75 s) of the Geotail/WaveForm Capture in the neutral plasma sheet where β  > 1 on 10:20 UT, 2 February 1996. The tripolar ESW is suggested to be one kind of steady‐going solitary structure. More than 200 waveforms with clear tripolar characteristics are differentiated for statistical analysis, and result shows that (1) their amplitude is within 100–>500 μV/m, with an average amplitude of about 254 μV/m; (2) the pulse width of the tripolar ESWs is 0.5–1.0 ms, with an average value of about 0.75 ms; (3) it is asymmetrical in both the amplitude and pulse width of the tripolar ESWs: most part of the tripolar ESWs (about 76.5%) are asymmetrical in the amplitude of one hump and the other one, and more than 75% (about 177 amount the 236 waveforms) of the tripolar ESWs are asymmetrical in the time duration of the two humps in the waveform; (4) most of the tripolar ESWs are with the potential humps of 10–60 mV, small ratio of them with potential humps larger than 100 mV. The tripolar ESWs with net potential drop of about 10–50 mV can be interpreted as "weak" double layers. The possible generation mechanism of tripolar ESWs and their role in reconnection are discussed by studying the particle distribution during which the tripolar ESWs are continuously observed. The observation of tripolar ESWs presents evidence of complex structure of electron holes within the reconnection diffusion region and is helpful to the understanding of the energy release process of reconnection. Key Points: first observation of tri‐polar ESWs associated with the magnetic reconnection statistical analyses of tri‐polar ESWs in detail asymmetry both in the amplitude and pulse width of the tri‐polar ESWs